PENGARUH PENGGUNAAN MODEL PEMBELAJARAN LANGSUNG DAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR IPA PADA SISWA KELAS III SD - Hilda Oktri Yeni; Dirneti; Anggri Dwi Nata; Rahmat Sanusi; Edi Kurniawan; Misiana (Universitas Karimun Prodi S1 Pendidikan Luar Biasa, 2023)
The problem in this study is that science learning outcomes are still low, especially the material on Characteristics of Living Things and the Needs of Living Things in Class III Students of SD Negeri 002 Tebing Karimun. This study aims to determine the effect of using the direct learning model (Rirect Instruction) and the STAD Type Cooperative Learning Model (Student Teams Achievement Division) on Science Learning Outcomes Material Characteristics of Living Things and the Needs of Living Things in Class III Students of SD Negeri 002 Tebing Karimun. This type of research used in research is quantitative research with a quasi-experimental approach. The population in this study were all students of class III SD Negeri 002 Tebing Karimun, totaling 68 students. The sampling technique used is saturated samples. The sample in this study were 34 students of class IIIb with a direct learning model (Rirect Instruction) and 34 students of class IIIA Cooperative Learning Type Stad (Student Teams Achievement Division). The instrument used in this study was an objective test with 20 questions. The data analysis technique was carried out by statistical tests using the t test Based on data analysis, it can be seen that: 1) There is a significant effect of the use of the direct learning model (Rirect Instruction) on Science Learning Outcomes Material Characteristics of Living Things and Needs of Living Things in Class III Students of SD Negeri 002 Tebing Karimun Academic Year 2016/2017, with tcount 5 .79 > ttable 2.03. 2) There is a significant influence of the use of the Stad Type Cooperative Learning Model (Student Teams Achievement Division) on Science Learning Outcomes Material Characteristics of Living Things and Needs of Living Things in Class III Students of SD Negeri 002 Tebing Karimun in the 2016/2017 Academic Year, with tcount 6.21 > ttable 2.03. Significant Influence of the use of the direct learning model (Rirect Instruction) and the STAD Type Cooperative Learning Model (Student Teams Achievement Division) on Science Learning Outcomes Material Characteristics of Living Things and the Needs of Living Things in Class III Students of SD Negeri 002 Tebing Karimun academic year 2016/2017, with tcount 3.14 > ttable 1.995